2015
DOI: 10.3855/jidc.4563
|View full text |Cite
|
Sign up to set email alerts
|

Potential spread of multidrug-resistant coagulase-negative staphylococci through healthcare waste

Abstract: Introduction: Healthcare waste (HCW) might potentially harbor infective viable microorganisms in sanitary landfills. We investigated the antimicrobial susceptibility patterns and the occurrence of the mecA gene in coagulase-negative Staphylococcus strains (CoNS) recovered from the leachate of the HCW in an untreated sanitary landfill. Methodology: Bacterial identification was performed by physiological and molecular approaches, and minimum inhibitory concentrations (MICs) of antimicrobial drugs were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Similar results were reported in a study performed between 2000 and 2009 in a hospital in Kenya, where in blood samples collected from neonates, S. epidermidis accounted for 33% of the isolated strains [15]. Furthermore, a study carried out in Brazil showed that 2.7% of S. epidermidis strains were isolated from hospital healthcare wastes, indicating a potential risk of spread outside the hospital setting [16].…”
Section: Staphylococcus Epidermidis Spreadsupporting
confidence: 74%
“…Similar results were reported in a study performed between 2000 and 2009 in a hospital in Kenya, where in blood samples collected from neonates, S. epidermidis accounted for 33% of the isolated strains [15]. Furthermore, a study carried out in Brazil showed that 2.7% of S. epidermidis strains were isolated from hospital healthcare wastes, indicating a potential risk of spread outside the hospital setting [16].…”
Section: Staphylococcus Epidermidis Spreadsupporting
confidence: 74%
“…The extent to which fomites contribute to overall rates of nosocomial infection remains unknown. However, fomites play a notable role in the transmission of Gram-positive and Gram-negative bacterial pathogens, including staphylococcal species ( Nascimento et al 2015 ).…”
mentioning
confidence: 99%
“…Fomite surfaces that are transported between hospital rooms are of particular concern and have been implicated in nosocomial outbreaks caused by different genera and species, including methicillin-resistant Staphylococcus aureus (MRSA) ( Cohen et al 1997 , Nascimento et al 2015 , Zargaran et al 2015 ). Since the 1970s, only a few studies have investigated the contamination of fomites by coagulase-negative staphylococci (CoNS), predominantly Staphylococcus epidermidis ( Lowbury et al 1971 , Saito et al 2014 , Zargaran et al 2015 ).…”
mentioning
confidence: 99%
“…Por otro lado, el gen mecA se ha encontrado en especies coagulasa negativo no responsable de procesos patógenos en los que presumiblemente no debería haberse utilizado una terapia antibiótica, y pueden actuar como reservorio de la resistencia a largo plazo (Nascimento et al, 2015;Zong et al, 2011).…”
Section: Discussionunclassified